2017
DOI: 10.1038/s41598-017-06835-3
|View full text |Cite|
|
Sign up to set email alerts
|

Sirt1 negatively regulates FcεRI-mediated mast cell activation through AMPK- and PTP1B-dependent processes

Abstract: Sirt1, a key regulator of metabolism and longevity, has recently been implicated in the regulation of allergic reactions, although the underlying mechanism remains unclear. Here we show that Sirt1 negatively regulates FcεRI-stimulated mast cell activation and anaphylaxis through two mutually regulated pathways involving AMP-activated protein kinase (AMPK) and protein tyrosine phosphatase 1B (PTP1B). Mast cell-specific knockout of Sirt1 dampened AMPK-dependent suppression of FcεRI signaling, thereby augmenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 57 publications
3
22
1
Order By: Relevance
“…A previous study reported that NR4A1 suppresses AMPK phosphorylation at Thr172 by inhibiting LKB1 binding to AMPK in human hepatocytes . Since the LKB1/AMPK axis negatively regulates mast cell activation, we examined the impact of NR4A1 knockdown (Figure A), knockout (Figure B), and overexpression (Figure C) on LKB1/AMPK signaling in BMMCs. As reported previously, LKB1 and AMPK were constitutively active in mast cells, and IgE/Ag stimulation reduced their phosphorylation, resulting in efficient activation of FcεRI signaling components including PLCγ1, ERK, JNK, and IKK, but not Akt, p38 MAPK, or Syk, a primary FcεRI‐proximal tyrosine kinase.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study reported that NR4A1 suppresses AMPK phosphorylation at Thr172 by inhibiting LKB1 binding to AMPK in human hepatocytes . Since the LKB1/AMPK axis negatively regulates mast cell activation, we examined the impact of NR4A1 knockdown (Figure A), knockout (Figure B), and overexpression (Figure C) on LKB1/AMPK signaling in BMMCs. As reported previously, LKB1 and AMPK were constitutively active in mast cells, and IgE/Ag stimulation reduced their phosphorylation, resulting in efficient activation of FcεRI signaling components including PLCγ1, ERK, JNK, and IKK, but not Akt, p38 MAPK, or Syk, a primary FcεRI‐proximal tyrosine kinase.…”
Section: Resultsmentioning
confidence: 99%
“…Since the LKB1/AMPK axis negatively regulates mast cell activation, we examined the impact of NR4A1 knockdown (Figure A), knockout (Figure B), and overexpression (Figure C) on LKB1/AMPK signaling in BMMCs. As reported previously, LKB1 and AMPK were constitutively active in mast cells, and IgE/Ag stimulation reduced their phosphorylation, resulting in efficient activation of FcεRI signaling components including PLCγ1, ERK, JNK, and IKK, but not Akt, p38 MAPK, or Syk, a primary FcεRI‐proximal tyrosine kinase. Notably, phosphorylation of LKB1/AMPK and its downstream mediator acetyl‐CoA carboxylase (ACC) was significantly increased by siRNA silencing (Figure A) and genetic knockout (Figure B) of NR4A1, whereas it was conversely decreased by adenoviral overexpression of NR4A1 (Figure C), suggesting that NR4A1 attenuates LKB1/AMPK signaling in BMMCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings raise the interesting possibility that if AG-30/5C activates human MC via MRGPRX2, it may act either as a balanced or biased agonist for the receptor. The stilbenoid resveratrol activates sirtuin 1 (sirt1) to inhibit IgEmediated MC degranulation (33). A recent screen of the National Institutes of Health (NIH) Clinical Collection library led to the identification of resveratrol as an inhibitor of MRGPRX2-mediated Tango (34).…”
mentioning
confidence: 99%